Tra ricezione e rielaborazione del passato: un exemplum moderno. Gea di Luca Enoch. - Castello, Maria G. (Status Quaestionis, 2015)
The article aims to analyse the reception of classical antiquity and of the ancient religions in a comic by Luca Enoch: Gea. Originally published by Sergio Bonelli Editore in the late 1990s, Gea is an unicumfor the Bonellian standards starting from its editorial format and its narrative structure. But the real touch of originality can be identified in its main themes, which are unusual for a “popular comic” – sexuality, social problems, political matters, etc. – and in the way how the Author uses the classical heritage and the ancient religions in two different modes. The former is presented in a traditional and stereotypical way while the latter are strongly reinterpreted. So the purpose of this paper is to understand the reasons for this different use of the past.